Spectroscopic and Computational Insight into the Intermolecular Interactions between Zwitter-Type Ionic Liquids and Water Molecules - Park, HoSeok; Jung, Young Mee; Yang, Seong Ho; Shin, Weonho; Kang, Jung Ku; Kim, Hoon Sik; Lee, Hyun Joo; Hong, Won Hi (WILEY-V C H VERLAG GMBH, 2010)
Geometric and conformational changes of zwitter-type ionic liquids (ZILs) due to hydrogen-bonding interactions with water molecules are investigated by density functional theory (DFT), two-dimensional IR correlation spectroscopy (2D IR COS), and pulsed-gradient spin-echo NMR (PGSE NMR). Simulation results indicate that molecular structures in the optimized states are strongly influenced by hydrogen bonding of water molecules with the sulfonate group or imidazolium and pyrrolidinium rings of 3-(1-methyl-3-imidazolio)propanesulfonate (1) and 3-(1-methy1-1-pyrrolidinio)propanesulfonate (2), respectively. Concentration-dependent 2D IR COS reveals kinetic conformational changes of the two ZIL-H2O systems attributable to intermolecular interactions, as well as the interactions of sulfonate groups and imidazolium or pyrrolidinium rings with water molecules. The dramatic changes in the H-1 self-diffusion coefficients elucidate the formation of proton-conduction pathways consisting of ZIL networks. In ZIL domains, protons are transferred by a Grotthuss-type mechanism through formation, breaking, and restructuring of bonds between ZILs and H2O, leading to an energetically favorable state. The simulation and experimental investigations delineated herein provide a perspective to understanding the interactions with water from an academic point of view as well as to designing ILs with desired properties from the viewpoint of applications.
Keywords: SELF-DIFFUSION; SILVER COMPLEXES; ORBITAL METHODS; FIELD GRADIENT; MOLTEN-SALT; TRANSPORT; CONDUCTION; HYDROGEN; ORGANIZATION; SIMULATION